OPTIMIZING MOLECULAR TECHNIQUES FOR ACCURATE EXAMINATION OF LEPTOSPIRA SPECIES: A COMPREHENSIVE PRIMER FOR RESEARCHERS - Aldiana Astuti; Farida Dwi Handayani (Journal of Vocational Health Studies)
Background: Leptospirosis is a potentially life-threatening disease caused by bacteria of the genus Leptospira. The accurate identification and characterization of Leptospira species are critical for disease surveillance, outbreak investigation, and treatment strategies. Molecular techniques, such as Polymerase Chain Reaction (PCR) and Deoxyribonucleic acid (DNA) sequencing, have revolutionized the field of microbiology, providing rapid and accurate identification of Leptospira strains. However, optimizing these molecular techniques for accurate examination of Leptospira species can be challenging due to the genetic diversity and complexity of these bacteria. Purpose: This research aims to identify the most suitable primers for the precise identification of pathogenic Leptospira strains. Method: This research used the PCR method, using LipL32, rrs2, seqY, LipL41, IcdA, and Adk primers. A total of 17 isolates of pathogenic Leptospira bacteria were cultured from Institute of Vector Control and Reservoir Disease (IVRCD) in Salatiga, Indonesia. Result: The results of the research showed that the LipL41 and IcdA primers were found to be effective in distinguishing pathogenic strains, while the seqY, LipL32, Adk, and rrs2 primers required further refinement. The suitable Melting Temperature (TM) or annealing temperature is 58°C with 35 cycles of amplification. DNA concentration and purity had an A260/A280 ratio ranging between 1.8 and 2.8. Conclusion: LipL41 (500 bp) and IcdA (700 bp) are suitable primers for identifying pathogenic Leptospira.